A case study of PTFE@SiO2 core-shell solid lubricant. (August 2021) - Wang, Na; Wang, Honggang; Ren, Junfang; Gao, Gui; Zhao, Gengrui; Yang, Yawen; Wang, Jinqing; Yang, Shengrong
Abstract: In this paper, the wear and transfer behaviors of polytetrafluoroethylene@silica (PTFE@SiO2 ) core-shell composite particles filled epoxy resin (PTFE@SiO2 -EP) coating during the sliding were studied in detail. The main results indicated that: firstly, the addition of PTFE@SiO2 particles can result in favorable plastic deformation on the worn surface; secondly, the morphology of PTFE@SiO2 particles in-situ changes from pressed to broken to flattened, and the average friction coefficient, wear rate as well as the transfer film thickness of the PTFE@SiO2 -EP coating all conform to the following regularity: run-in period > steady-state period > transition period. Besides, except that FeF2 is not contained in the transition period, the compositions of the transfer film are basically unchanged during the whole friction process, which all consist of PTFE, ploy (methylmethacrylate-co-3-(trimethoxysilyl) propylmethacrylate) (P(MMA-co-MPS)), SiO2, EP and FeF2 . Additionally, no wear debris is observed during the whole sliding. It is expected that this study can provide instructive scientific guidance for the lubrication behaviors of soft@hard core-shell additives, and further enrich the tribological theories of solid lubricants with core-shell structure. Highlights: A favorable plastic deformation appears on the PTFE@SiO2-EP coating surface. The morphology of PTFE@SiO2 particles in suit changes from pressed to broken to flattened. PTFE@SiO2-EP coating generates transfer film in the whole friction process. The transfer film always contains PTFE, SiO2, P(MMA-co-MPS) and EP. There is no wear debris generated during the whole friction process.